A designed antimicrobial peptide with potential ability against methicillin resistant Staphylococcus aureus - Yuan, Bingqian; Lu, Xiaoyu; Yang, Min; He, Qiyi; Cha, Zhuocen; Fang, Yaqun; Yang, Yan; Xu, Lei; Yan, Jingting; Lai, Ren; Wang, Aili; Yu, Xiaodong; et al. (Frontiers in Microbiology, 2022)
Staphylococcus aureus (S. aureus) is a Gram-positive pathogenic bacterium, which persistently colonizes the anterior nares of approximately 20-30% of the healthy adult population, and up to 60% is intermittently colonized. With the misuse and overuse of antibiotics, large-scale drug-resistant bacteria, including methicillin-resistant S. aureus (MRSA), have been appeared. MRSA is among the most prevalent pathogens causing community-associated infections. Once out of control, the number of deaths caused by antimicrobial resistance may exceed 10 million annually by 2050. Antimicrobial peptides (AMPs) are regarded as the best solution, for they are not easy to develop drug resistance. Based on our previous research, here we designed a new antimicrobial peptide named GW18, which showed excellent antimicrobial activity against S. aureus, even MRSA, with the hemolysis less than 5%, no cytotoxicity, and no acute toxicity. Notably, administration of GW18 significantly decreased S. aureus infection in mouse model. These findings identify GW18 as the ideal candidate against S. aureus infection.